ANALISIS PERAN POKJAR MADINAH DALAM MENDUKUNG PENDIDIKAN KESTARAAN (PAKET A/B/C) BAGI ANAK-ANAK INDONESIA DI MADINAH, ARAB SAUDI - Amara Salwa; Munawir Pasaribu (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
Indonesian children in Medina, Saudi Arabia face serious obstacles in accessing formal education with a national curriculum due to administrative limitations, cross-border regulations, and high private school fees. This descriptive qualitative study aims to analyze the role of POKJAR Madinah in supporting Package A, B, and C equivalency education, describe the implementation of its programs, and identify supporting and inhibiting factors through direct observation, semi-structured interviews, and documentation validated by triangulation of sources, techniques, and time. POKJAR Madinah, which has been officially affiliated with PKBM Sekolah Indonesia Jeddah since 2018, provides a combination of online and face-to-face learning based on the Merdeka Curriculum with local Arabic content, and has proven to be the only legal education alternative for Indonesian children in Madinah. The dedication of volunteer tutors and community support are key enabling factors, while the absence of post-pandemic government institutional funding is a critical obstacle. This study concludes that the sustainability of POKJAR Madinah is highly dependent on systematic government funding policy interventions.